(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
This article provides information about the ways of being and acting of women in the Vale do Itajaí, Santa Catarina, during the 20th Century, based on the memories of four women who were interviewed in 2021, for the elaboration of the documentary “Fashion and Memories in the Vale”. The documentary sought out mnesic records of these women related to the works and modes that permeated fashion during the 20th century in the Vale, resulting in knowledge built on the obligations at work, at home and in the daily lives of the interviewees. This article aimed to highlight an identity construction in the Itajaí Valley, based on the interviewees’ memories of their dress habits, manual labor and professions, as well as the manners and fashions of their time, based on a content analysis (BARDIN, 2016), in which the interviewees’ statements will be presented. It is expected to contribute to the expansion of the fields of study of fashion in Santa Catarina, enabling the use of records and memories of local fashion in teaching, research and extension.